The Relationship Between Self-Control and Self-Esteem with Narcissistic Behavior in Teenage Tiktok Users - Lenny Syamsuddin; Salahudin Liputo; Regina Saleh (Borong Newinera Publisher, 2024)
This research aims to determine the relationship between self-control and self-esteem and narcissistic behavior in adolescent Tiktok users at SMA Negeri 2 Gorontalo City. This research uses a correlational quantitative design with a population of 840 students, a sample size of 90 students using purposive sampling techniques. The data collection method uses a self-control scale, self-esteem scale and narcissistic behavior scale using multiple correlation analysis techniques (Multivariate Correlation) with the SPSS 23.0 for Windows program. Data analysis on the correlation coefficient between self-control variables and narcissistic behavior resulted in a value of R = -0.514 p = 0.000 and the relationship between self-esteem and narcissistic behavior was R = -0.668 p = 0.000. This means, it can be said, there is a significant negative relationship between self-control and narcissistic behavior and there is also a significant negative relationship between self-esteem and narcissistic behavior in teenage TikTok users. Furthermore, the results of multiple correlations to measure the relationship between self-control and self-esteem with narcissistic behavior obtained a value of R = 0.670, R Square 0.449 and p = 0.000 (p < 0.05). This is shows, there is a relationship between self-control and self-esteem and narcissistic behavior in teenage TikTok users at SMA Negeri 2 Gorontalo City.